2019
DOI: 10.3390/medicina55050132
|View full text |Cite
|
Sign up to set email alerts
|

Possible Serological Markers to Predict Mortality in Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: Background and objectives: Idiopathic pulmonary fibrosis (IPF) has a particularly poor prognosis, and most IPF-related deaths are due to acute exacerbation (AE) of this condition. Few reports about biomarkers to predict prognosis of AE-IPF have been published since the release of the new AE-IPF criteria in 2016. The present study investigated relationships between serological markers and in-hospital mortality after the onset of AE-IPF. Methods: Demographic, serological, and imaging data from patients hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Comparisons of categorical data between the pirfenidone and nintedanib groups were performed using Fisher’s exact test. Continuous variables were analyzed using the Mann–Whitney U test and denoted by the median (maximum and minimum) [ 18 , 19 ]. Survival time was analyzed using the Kaplan–Meier method and compared between groups using the log-rank test.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons of categorical data between the pirfenidone and nintedanib groups were performed using Fisher’s exact test. Continuous variables were analyzed using the Mann–Whitney U test and denoted by the median (maximum and minimum) [ 18 , 19 ]. Survival time was analyzed using the Kaplan–Meier method and compared between groups using the log-rank test.…”
Section: Methodsmentioning
confidence: 99%
“…The impaired synthesis of phospholipids and cholesterol affects the lung surfactant synthesis and alveolar homeostasis by disrupting the epithelial barrier integrity and promoting fibrogenesis [ 184 ]. Increased levels of lipids and plasmatic cholesterol have been linked to disease acute exacerbation and high mortality in IPF subjects [ 185 ]. In this regard, mitochondrial MFN1 and MFN2 play a crucial role in regulating lipids and cholesterol production and their knockdown affect lipid synthesis in AEC2 cells and exacerbates bleomycin-induced lung fibrosis [ 184 ].…”
Section: Cellular and Molecular Mechanisms In Ipfmentioning
confidence: 99%
“…A high baseline total serum cholesterol appeared protective against the development of IPF in our participants with Type 2 diabetes. Consistent with this observation, a Japanese study showed that the total serum cholesterol was a negative associate of acute IPF exacerbations and mortality 13 . The positive relationship between age at diabetes diagnosis and IPF may represent a healthy survivor effect, with younger adults who develop diabetes being susceptible to cardiovascular death before reaching the older age groups in which the risk of IPF is relatively high 11 .…”
Section: Discussionmentioning
confidence: 74%